2020
DOI: 10.1002/jaal.1058
|View full text |Cite
|
Sign up to set email alerts
|

Reading Motivation in High School: Instructional Shifts in Student Choice and Class Time

Abstract: Student choice and restructured class time are classic motivators for positive literary experiences, but are they still applicable in a contemporary high school setting? Revisiting Transactional Theory Frameworks and PracticesRosenblatt's (1995) transactional theory describes reading teachers' tasks as creating fertile classroom environments where fruitful student transactions with texts can occur. She noted that teachers facilitate positive reading experiences and promote greater levels of reading satisfactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…Consequently, when teachers, already in the early grades, make sure that students read extensively to develop their competence and encourage and challenge them to read what they see as interesting and meaningful texts, students are more likely to start to identify themselves as readers and to develop more autonomous motivation and self-determined behaviour. As seen earlier, our results indicate that students want to be good readers, and in line with SDT, schools must strive to make them feel like good readers, since positive experiences will have an impact on their future level of motivation and, in turn, affect their attitudes, beliefs and perceptions (Allred & Cena, 2020;Guthrie et al, 2001).…”
supporting
confidence: 63%
“…Consequently, when teachers, already in the early grades, make sure that students read extensively to develop their competence and encourage and challenge them to read what they see as interesting and meaningful texts, students are more likely to start to identify themselves as readers and to develop more autonomous motivation and self-determined behaviour. As seen earlier, our results indicate that students want to be good readers, and in line with SDT, schools must strive to make them feel like good readers, since positive experiences will have an impact on their future level of motivation and, in turn, affect their attitudes, beliefs and perceptions (Allred & Cena, 2020;Guthrie et al, 2001).…”
supporting
confidence: 63%
“…For example, an intervention in 44 elementary classrooms (Fisher & Frey, 2018) showed that providing students with access to better books and choice in what to read, engaging students in text discussions, and having the teacher and students publicly introduce books through book talks increased students’ reading interest (as documented by teacher observations and library book check‐outs). Similarly, Allred and Cena (2020) found that opportunities for independent, self‐selected reading produced statistically significant positive changes across time in adolescents’ attitudes toward reading, as well as in their reading self‐efficacy.…”
Section: What Kinds Of Readers Should Society Raise?mentioning
confidence: 89%
“…Providing access to text, offering choices in text selection, and curating texts relevant to students’ lives and interests can all contribute to positive literate dispositions (Allred & Cena, 2020; Ivey & Johnston, 2013). For example, an intervention in 44 elementary classrooms (Fisher & Frey, 2018) showed that providing students with access to better books and choice in what to read, engaging students in text discussions, and having the teacher and students publicly introduce books through book talks increased students’ reading interest (as documented by teacher observations and library book check‐outs).…”
Section: What Kinds Of Readers Should Society Raise?mentioning
confidence: 99%
“…Again, in order to improve student's selfconcepts teachers may design means of sparking students' interest in learning, demonstrating its relevance, and providing them with feedback in order to raise their expectation of success in the classroom. Teachers can promote students' learning pleasure by being kind and responsive to their needs which will boost students' selfconcepts and lead to better academic performance of students (Allred, & Cena, 2020).…”
Section: Hypothesismentioning
confidence: 99%